Comprehensive Characterization of Shredded Lithium‐Ion Battery Recycling Material. Issue 22 (14th March 2022) - Peschel, Christoph; van Wickeren, Stefan; Preibisch, Yves; Naber, Verena; Werner, Denis; Frankenstein, Lars; Horsthemke, Fabian; Peuker, Urs; Winter, Martin; Nowak, Sascha
Abstract: Herein we report on an analytical study of dry‐shredded lithium‐ion battery (LIB) materials with unknown composition. Samples from an industrial recycling process were analyzed concerning the elemental composition and (organic) compound speciation. Deep understanding of the base material for LIB recycling was obtained by identification and analysis of transition metal stoichiometry, current collector metals, base electrolyte and electrolyte additive residues, aging marker molecules and polymer binder fingerprints. For reversed engineering purposes, the main electrode and electrolyte chemistries were traced back to pristine materials. Furthermore, possible lifetime application and accompanied aging was evaluated based on target analysis on characteristic molecules described in literature. With this, the reported analytics provided precious information for value estimation of the undefined spent batteries and enabled tailored recycling process deliberations. The comprehensive feedstock characterization shown in this work paves the way for targeted process control in LIB recycling processes. Abstract : Comprehensive characterization of shredded lithium‐ion battery (LIB) recycling material was performed. As a result, a toolbox for analysis of these complex samples compromising various electrolyte, active and inactive materials is provided. By means of extraction and pyrolysis with subsequent chromatography and mass spectrometry‐based analyses for example identification of hazardous species and polymer binder residues on trace level was enabled. Thus, detailed feedstock characterization serves as a starting point for risk assessment, tailored material treatment and targeted process control within LIB recycling. Comprehensive Characterization of Shredded Lithium‐Ion Battery Recycling Material (Nowak et al.) #ProjektDEAL